The Effect of Job Training on Employee Performance Mediated by Employee Quality in The Employment BPJS Branch In Medan Raya - Sakinah Ramza; Mesra B (Neo Journal of economy and social humanities, 2024)
In this study, researchers wanted to see the direct and indirect effects between training variables as independent variables and employee quality as mediating variables and employee performance as the dependent variable. This type of research uses quantitative, this research was conducted at the BPJS Employment BPJS Branch Office in Greater Medan which consists of BPJS Employment Medan City Branch Office, Branch, North Medan, Tanjung Morawan Branch and Binjai Branch. The population of this study was 80 employees and the sample used was all the population using the saturated sample technique. The data source used is primary data sources and data collection is done by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows Job training has a positive and significant effect on employee performance with an original sample value of 0.463 and P values of 0.000. Job training has a positive and significant effect on employee quality with an original sample value of 0.590 and p values of 0.000. Employee quality has a positive and significant effect on employee performance with an original sample value of 0.511 and p values of 0.000. Job training has a positive and significant effect on employee performance through employee quality directly with original sample results of 0.302 and p values of 0.000